Analysis Of The Critical Discourse Of The Mata Najwa Program "Gubernur Aceh Bicara" On Najwa Shihab's Youtube Channel - Raja Khairanda Siregar; Anang Anas Azhar (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study aims to analyze the construction of leadership discourse in handling the 2025 Sumatra flood disaster as presented in the Mata Najwa program episode “Gubernur Aceh Bicara” (Aceh Governor Speaks) on Najwa Shihab's YouTube channel. The flood that hit Aceh was not only an ecological crisis but also a space for public communication that showed how the government explained the disaster conditions, responded to criticism, and built leadership legitimacy in front of the public. This study uses a descriptive qualitative approach with Teun A. van Dijk's critical discourse analysis method, which emphasizes the relationship between text structure, social cognition, and social context. The research data comes from the dialogue between Najwa Shihab and the Governor of Aceh in the program, which was analyzed using content analysis techniques to identify themes, language choices, and communication strategies that emerged in the conversation. The results show that leadership discourse is constructed through several main patterns, namely the representation of the disaster as a major crisis, the emphasis on the humanitarian impact, the narrative of regional recovery, the explanation of obstacles to aid distribution, and the communication of the needs of the affected communities. The use of diction such as “second tsunami,” descriptions of the victims' conditions, and explanations of infrastructure damage served to reinforce the public's perception of the scale of the crisis. The structure of the dialogue also showed a shift in the narrative from a discussion of the impact of the disaster to an affirmation of the government's performance in the recovery process. From a social cognition perspective, this discourse shapes the understanding that local governments are actively trying to deal with the crisis. In a social context, digital media becomes a space for regional heads to build their leadership image and political legitimacy through disaster communication. The findings of this study show that political talk shows in digital media serve as an arena for the production of discourse that influences public perception of disasters and government leadership.